Estimated Cardiorespiratory Fitness Is Associated With Reported Depression in College Students - Jalene, Sharon; Pharr, Jennifer; Shan, Guogen; Poston, Brach (Frontiers in Physiology, 2019)
Depression is a serious but treatable health issue that affects college students at an alarming rate. Improved cardiorespiratory fitness (CRF) decreases depression risk and severity but this relationship has not been fully evaluated in the college student population. Non-exercise estimated CRF (eCRF) could be used to identify students at risk for or suffering from depression. This study investigated the associations of depression and eCRF in college students. Participants (N = 437) completed a survey which included demographic and student-status questions, eCRF variables, and a validated depression instrument. Descriptive, chi-square, t-test, regression, and odds ratio analyses were employed. Depression was associated with low-fitness (X2 = 4.660, P = 0.031) and eCRF below age-predicted CRF (t = 3.28, P < 0.001). Predictors of increased depression included low-fitness, sexual orientation, current depression treatment, and GPA (R2= 0.145-0.159; Adj R2= 0.135-0.149). Odd ratio analyses determined that low-fitness increased the risk of reporting depression ( ß=2.39, P = 0.017, 95% CI=1.17-4.872) which remained significant when adjusted (ß=2.478, P=0.017, 95% CI=1.175-5.229). Adjusted odds ratio analyses also indicated increased risk of reporting depression for those in a sexual minority (ß=2.582, P=0.001, 95% CI=1.44,4.629) and undergoing current depression treatment (ß=2.393, P < 0.001, 95% CI=2.393-13.043). High levels of fitness did not reduce the odds of reporting depression compared to age predicted CRF. A simple eCRF algorithm can be used to identify college student depression.